A study to assess the nutritional status of children with cleft lip and/or cleft palate and its correlation with breast feeding at a tertiary health care centre - Sampagar, Abhilasha; Lakhkar, Bhavana; Sampagar, Ashok; Wagha, Jayanth (International Journal of Contemporary Pediatrics, 2018)
Background: Cleft lip with or without cleft palate is one of the most common congenital anomalies. In 2008, the World Health Organization included cleft lip and palate in their Global Burden of Disease initiative. The incidence of cleft lip and palate in India is enormous: one in 781 live births. The growth of children with these deformities is often impaired in comparison to healthy children. Several studies describe a growth lag in either weight or height of cleft children. The objective of the study was to observe the nutritional status of children with cleft lip and/or cleft palate and its correlation with breastfeeding. Methods: A cross sectional study was conducted at Department of Pediatrics, AVBRH Sawangi (Meghe), Wardha for the period of two years from August 2010 to March 2012. All children below 15 years with cleft lip and/or palate admitted in the pediatric ward, NICU or postnatal ward were included in the study. A Total of 200 children were included in the study and analyzed. Results: Male to female ratio was 1.4:1. The commonest type of defect was both the defects present together (62%) which was significantly more than individual defects (א2=23.98, p<0.0001). It was followed by isolated cleft lip (25.5%) and isolated cleft palate (12.5%). Malnutrition was more common in children who were deprived of breast milk (χ2=22.61, Significant). Significantly more children (69.6%) below the age group of 5 yrs were malnourished. (χ2=16. Significant). Conclusions: Our results confirm that, malnutrition is more prevalent in children with orofacial clefts. Lack of breast feeding is a significant contributor to severe malnutrition and recurrent infections in these children.